Association of time of breakfast and nighttime fasting duration with breast cancer risk in the multicase-control study in Spain - Palomar-Cros, Anna; Harding, Barbara N.; Espinosa, Ana; Papantoniou, Kyriaki; Pérez-Gómez, Beatriz; Straif, Kurt; Ardanaz, Eva; Fernández Villa, Tania; Amiano, Pilar; Gómez-Acebo, Inés; Moreno, Victor; Alguacil, Juan; et al. (Frontiers in Nutrition, 2022)
Circadian nutritional behaviors, defined by the daily eating / fasting cycle, have been linked with breast cancer. This study aims to further disentangle the association of nighttime fasting duration and time of breakfast with breast cancer risk. We analyzed data from 1,181 breast cancer cases and 1,326 population controls from the Spanish multi-case control study, 2008-2013. We collected circadian nutritional behaviors at mid-age via a telephonic interview. We applied logistic regression to estimate odds ratios (OR) and 95% confidence intervals (CI) for the association of nighttime fasting duration and time of breakfast with breast cancer risk in all women and stratified by menopausal status. Models were adjusted for age, center, education, family history of breast cancer, age at menarche, number of children, breastfeeding and age at first child, body mass index, contraceptive use and hormonal replacement therapy. A later time of breakfast was associated with a non-significant increased risk of breast cancer (OR=1.05, 95% CI 0.95-1.16, per hour increase). This association was stronger among premenopausal women, among whom each hour later in the time of breakfast was associated with an 18% increase in breast cancer risk (OR=1.18, 95% CI 1.01-1.40). The association was not observed in postmenopausal women. We did not observe an association with nighttime fasting duration and breast cancer risk after adjusting for time of breakfast. In this study, late breakfast was associated with increased breast cancer risk, compared to early breakfast. Aside from nutritional quality, circadian nutritional behaviors should be further studied in relation with cancer.